Study guides

☆☆

Q: Factor the polynomial expression 13x2 minus 65x plus 78?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x3 + 13x2 + 42x = x(x + 6)(x + 7).

no. it can be simplified into 13x2. 13 and 2 are prime.

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

x2 + 12x2 + 35 = 13x2 + 35 which cannot be factorised in any sensible way.

2x4 - 9x3 + 13x2 - 15x + 9 = 2x4 - 6x3 - 3x3 + 9x2 + 4x2 - 12x - 3x + 9 = 2x3(x - 3) - 3x2(x - 3) + 4x(x - 3) - 3(x - 3) = (x - 3)*(2x3 - 3x2 + 4x - 3) So the quotient is (2x3 - 3x2 + 4x - 3) and the remainder is 0.

Related questions

2x^3 - 3x^2 + 4x - 3

4x4 + 13x2 + 36 is a quadratic in x2. The discriminant is 132 - 4*4*36 = -407. Since the discriminant is negative, the expression has no real roots and so it cannot be factorised (in the normal sense of the term).

-x2(5x5 + 13)

X3 + 13X2 + 40X factor out an X X(X2 + 13X + 40) factor the quadratic expression, what two factors of 40 add up to 13? X(X + 8)(X + 5) works the same if that is a negative in front of X3, just sign changes

13x2=26 By Someone?

(x - 2)(x + 2)(x - 3)(x + 3)

13x2

26. 13x2=26.

26

x3 + 13x2 + 42x = x(x + 6)(x + 7).

There aren't any common factors, which makes the GCF 1. This is meaningless to factor out, since it leaves the original equation. If you meant to write -5x7, that makes the common factor -x2 and leaves (5x5 + 13)

13x2 2x13

People also asked